A qualitative study on ageing related anxiety among middle aged women in Malaysia - Minhat, Halimatus Sakdiah; Sahharon, Hamizah; Mohd Zulkefli, Nor Afiah (Malaysian Public Health Specialist Association, 2015)
Ageing anxiety is commoner among women compared to men. However, little is known on the possible contributing factors towards the development of ageing related anxiety among Malaysian women. This study aimed to explore ageing anxiety among the middle-aged women in Malaysia in facing the ageing process. Series of 6 focus group discussions (FGD) were conducted involving a total of 36 women aged between 35 and 59 years old. Each FGD consisted of 5 to 7 respondents and was conducted for an average of 1 to 2 hours. The respondents were selected using the maximum variation sampling method focussing on five age categories, between 35 to 39, 40 to 44, 45 to 49, 50 to 54 and 55 to 59 years old. Representative from several residential areas in the area of Putrajaya Federal Territory and Seri Kembangan, Selangor were involved in the selection of respondents. The interviews revealed that, majority of the respondents were seriously thinking of the possible negative experiences associated with ageing and being old, but very few experiencing ageing anxiety. Three main themes that were identified to contribute to the ageing anxiety were issues related to caregiving at old age and fear of loneliness, the welfare and care of their children when they are old and eventually die and also physical changes that occurred with ageing process. These themes were not specifically associated with any particular age groups, marital or income status. However, the development of the ageing anxiety was found to be related to their personal experiences and observations from the surrounding community. The findings show that women in Malaysia are still emphasizing on the importance of traditional caregiving system, where elderly parents are looked after by the children or extended family members rather than living in formal institutions. Despite the important role of formal institutions in the care of elderly people in the future, it is still negatively perceived. With the shrinking of the size of nuclear family and massive involvement of women in employment sector, more elderly will be expected to reside in formal institutions in the near future. Relevant authorities should be made aware on the importance to maintain the quality of care in the formal institution for elderly, in order to tackle the negative perceptions.